Taxa de poupança e consumo no ciclo da vida das famílias Brasileiras: Evidência microeconômica - Marcos Antonio Coutinho da Silveira; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– With data from the Consumer Expenditure Survey of 2008-2209, the work assesses empirically the implications of the theory of life/permanent income for the behavior of the trajectories of consumption and savings rate of Brazilian families in the life cycle. The objective is to test the validity of the hypothesis of intertemporal consumption smoothing through access to the credit market, which in turn implies a negative savings rate for young and old families, when income is low, and a positive rate for middle aged families, when income is high. Assuming strong correlation between education and permanent income, the sample of households is divided into groups with different levels of education, since the ability of household debt may depend on your stock of wealth and human capital. The results reveal the existence of a strong parallel between income and current consumption for all levels of schooling, and this fact is more pronounced for the lower levels. As a consequence, the saving rate remains positive - for precautionary reason - practically throughout the life cycle. One possible explanation is that institutional barriers to access the credit market prevent Brazilian families from smoothing consumption through the life cycle.
Keywords: C20; E21; 330; consumption rate; life cycle